Dynamics of photosynthetic induction and relaxation within the canopy of rice and two wild relatives - Acevedo-Siaca, Liana G.; Dionora, Jacqueline; Laza, Rebecca; Quick, William Paul; Long, Stephen P. (Wiley, 2021)
Wild rice species are a source of genetic material for improving cultivated rice (Oryza sativa) and a means to understand its evolutionary history. Renewed interest in non‐steady‐state photosynthesis in crops has taken place due its potential in improving sustainable productivity. Variation was characterized for photosynthetic induction and relaxation at two leaf canopy levels in three rice species. The wild rice accessions had 16%–40% higher rates of leaf CO2 uptake (A) during photosynthetic induction relative to the O. sativa accession. However, O. sativa had an overall higher photosynthetic capacity when compared to accessions of its wild progenitors. Additionally, O. sativa had a faster stomatal closing response, resulting in higher intrinsic water‐use efficiency during high‐to‐low light transitions. Leaf position in the canopy had a significant effect on non‐steady‐state photosynthesis, but not steady‐state photosynthesis. The results show potential to utilize wild material to refine plant models and improve non‐steady‐state photosynthesis in cultivated rice for increased productivity.